Phytosterols from Haematococcus pluvialis: potential antioxidant and antiproliferative properties - Scodelaro Bilbao, Paola Gabriela (2015)
Haematococcus pluvialis is an oleaginous microalga proposed as a source of triacylglycerol (TAG) for biodiesel production. The aim of this work was to describe the effect of light-induced stress on lipid accumulation in a native strain. For this end, H. pluvialis CCALA 1081 from Bahía Blanca (Arg.) was grown under control conditions or light- induced stress (300 μmol m-2s -1 ) for 3, 6 and 12 days. Then, the lipid profile was analyzed in order to determine TAG and phytosterol (PHS) contents, the fatty acid profile of TAG and the composition of the PHS fraction. After 3 days of light-induced stress, TAG and PHS contents significantly increased with respect to control (210% and 1251%). Palmitic, oleic, linoleic and α linolenic fatty acids were increased whereas caproic acid content diminished in H. pluvialis under stress. Light-induced stress also reduced β-sitosterol content while clerosterol, brassicasterol and Δ7- campesterol augmented in the PHS fraction. No significant levels of lipid peroxidation were detected after 3 days of light-induced stress. Finally, PHS fraction displayed increased antioxidant capacity and, also, antiproliferative effect in human neuroblastoma cells. Our results show that light stress induces PHS accumulation in H. pluvialis with potential application as antioxidant and antiproliferative agents.